'African discourses' : the old and the new in post-apartheid isiZulu literature and South African black television dramas - Mhlambi, Innocentia Jabulisile (My University, 2009)
ABSTARCT This thesis sets out to explore the problematic perceptions regarding African indigenous language literature. The general view regarding this literature is that it is immature, irrelevant school-market driven and shows no artistic complexities and ingenuity.1 These disparaging remarks resonated persistently after the first democratic elections in 1994. Both local and international critics expected marked shifts in post-apartheid isiZulu literary productions because factors that hampered its development have been removed. The dominant Western and postcolonial critical approaches from which these critics articulated their views, operated on assumptions that failed to look at the role and centrality of the broader concerns usually covered by this literature. Barber (1994: 3) points out that these Western and postcolonial critical approaches, block a properly historical localized understanding of any scene of colonial and postindependence literary production in Africa. Instead it selects and overemphasized one sliver of literary and cultural production…and this is experience’. Furthermore it is the contention of this thesis that these critics used critical tools that are fundamentally mismatched for the types of narratives with which isiZulu literature and African-language literatures in general are engaged. It is the view of the author of this thesis that if a new set of critical tools are used, a paradigm shift may result which allows for revisiting creative conceptualisations involved in the production of these literatures. The primary aim of this thesis is to read post-apartheid isiZulu novels and the black television dramas using theoretical tenets postulated by Karin Barber. Barber’s research on African everyday culture is the key epistemological and cosmological framework with which to study post-apartheid literary and film productions that narrate the everyday life experiences of ordinary South Africans. The basic assumption is that orality which is the maximal point of reference for 1 See Mpahlele, 1992; Kunene, D. P. 1992 and 1994; Kunene, M. 1976 and 1991; and Chapman, 1996 any African work of imagination continues to thrive in black everyday popular culture as manifest in both print and broadcast media. The first part of this thesis deals with the use of oral genres in print media. Six novels are selected to explore the uses of proverbs, folktale motifs and naming as strategies for reading post-apartheid contemporary South African society. The thesis proceeds from an analysis of what these oral forms aim to achieve in the post-apartheid context. It is argued that through these oral verbal art forms the narratives transpose the traditional episteme and re-inscribe it for modern contemporary African society, where traditional morality is made to continue to shape and animate contemporary morality. The second section deals with the implications of some of these traditional epistemologies in broadcast media texts. Four post-apartheid black television dramas are selected. With Ifa LakwaMthethwa and Hlala Kwabafileyo, the thesis, demonstrates how these films position the middle-class as a solution to post-apartheid leadership challenges. The discussion of Gaz’ Lam and Yizo Yizo demonstrates the nature of orality, where oral texts are seen to be endlessly recycling similar themes in different media forms. The emphasis is on how renditions of texts always bring in new elements and topical issues, fresh and precise photographic capturing of key moments in society. In view of the nature of Barber’s theoretical model and that of isiZulu fiction and film, this thesis argues that it is the most appropriate to use for the analysis of Africanlanguages literatures. Barber’s theoretical model has intertextual links with the Black Film theoretical traditions in the Diaspora and the Third Cinema in Africa. These black film traditions, like Barber’s model, centralise the black experience, everyday culture and orality as the basic reference for African work of imagination and aesthetics.